Lovastatin Targets the USP14–Survivin Axis to Suppress Triple-Negative Breast Cancer via Ubiquitin-Mediated Proteasomal Degradation - Li Zhou; Chanjuan Zheng; Siyu Ding; Zhiyu Wang; Yiyuan Yang; Yian Wang; Guangchun He; Shujun Fu; Xiyun Deng (Cells)
Triple-negative breast cancer (TNBC), characterized by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor type 2 (HER2) expression, represents a therapeutic challenge due to its aggressive nature and limited treatment options. Here, we identified the cholesterol-lowering drug lovastatin (LV) as a potent apoptosis-inducing agent in TNBC. Mechanistically, LV disrupts the interaction between the deubiquitinating enzyme USP14 and Survivin, a key anti-apoptotic protein, enhancing polyubiquitination and the proteasomal degradation of Survivin. The overexpression of USP14 was found to stabilize Survivin and rescue LV-induced apoptosis and tumor suppression in vitro and in vivo, whereas USP14 silencing or inhibition with IU1 (a USP14-specific inhibitor) enhanced Survivin turnover and synergized with LV to suppress colony formation in TNBC cells. Clinical relevance was demonstrated through bioinformatic analysis and immunohistochemistry, revealing that elevated Survivin expression in TNBC tissues correlated with poor prognosis and is significantly upregulated in TNBC versus non-TNBC tissues. Our findings identify the USP14–Survivin axis as a potential therapeutic target and highlight LV as a promising candidate for TNBC treatment.